sbx/KB-bert-base-swedish-cased_PI-detection-detailed-iob - Szawerna, Maria Irena (University of Gothenburg, 2024)
A model based on KB/bert-base-swedish-cased trained to detect personal information, especially in learner essays. This variant differentiates between 38 detailed categories and differentiates between beginning and inside.

En modell baserad på KB/bert-base-swedish-cased tränad med syfte att upptäcka personliga uppgifter, särskilt i studentuppsatser. Den här varianten skiljer mellan 38 detaljerade kategorier samt markerar början och insidan.
sbx/KB-bert-base-swedish-cased_PI-detection-detailed-iob
Keywords: Language Technology (Computational Linguistics); PI detection; BERT; model; Natural Language Processing; Språkbehandling och datorlingvistik